RETINAL VEIN OCCLUSION IN A PATIENT WITH MATERNALLY INHERITED DIABETES AND DEAFNESS. (2017) - Sanfilippo, Christian J.; Prasad, Pradeep; Sarraf, David
Abstract : Purpose: To report a case of maternally inherited diabetes and deafness complicated by branch retinal vein occlusion and cystoid macular edema. Methods: Retrospective case report. Multimodal imaging including spectral domain optical coherence tomography, en face optical coherence tomography, and fundus autofluorescence was preformed, and the findings are presented. Findings: A 58-year-old female with a history of diabetes mellitus, hearing loss, and a previous diagnosis of age-related macular degeneration presented with decreased vision in the right eye. Clinical examination and multimodal imaging demonstrated a right inferior branch retinal vein occlusion complicated by cystoid macular edema and bilateral maculopathy suspicious for maternally inherited diabetes and deafness. Genetic testing confirmed an A3243G mitochondrial mutation. Conclusion: Multimodal retinal imaging is a key to guide diagnosis of rare genetic diseases such as maternally inherited diabetes and deafness. We report the unusual presentation of maternally inherited diabetes and deafness complicated by branch retinal vein occlusion and cystoid macular edema. Abstract : Maternally inherited diabetes and deafness is an inherited mitochondrial disorder caused by the A3243G mutation. We report a rare case of maternally inherited diabetes and deafness complicated by branch retinal vein occlusion.